Changes in Some Quality Criteria During Controlled Atmosphere (CA) Storage of Peaches - Eris, A.; Akbudak, B. (International Journal of Horticultural Science, 2001)
Intensive research has been implemented on different aspects of the bee pollination of pear in Hungary in the past decade, extending to the following topics: the effect of the opening sequence of the flowers within the inflorescence of pear cultivars on the effectiveness of bee pollination; the nectar production of flowers of pear cultivars; intensity of honeybee visitation and their foraging behaviour at the flowers of pear cultivars; flower constancy of honeybees to pear plantations; competition by weeds in bloom for bee pollination in flowering pear orchards; and some aspects to the bee pollination strategies of pear plantations (the effect of the limitation of bee pollination period on the set and the yield, possible compensation of frost damage of flowers by bee pollination in pear orchards, the optimal size of single cultivar block in pear plantations). The results of these studies are reviewed in this paper and some important aspects that need further studies are outlined.